A precarização do trabalho dos profissionais da atenção básica de saúde de um distrito sanitário de Campina Grande – PB - Oliveira Sobrinho, Nicodemus de (2017)
The precariousness of the work advances in contemporaneity and covers the most diverse sectors of the economy. The health sector has also seen an increase in precariousness in the various elements of its work process. In this sense, this paper analyzes the relation of the conditions and the work organization of the health professionals of the basic health units of a sanitary district of Campina Grande, with the precariousness of health work. It is a qualitative and analytical research carried out in three Basic Units of Family Health. The techniques of job observation, the application of questionnaires and semi-structured interviews were used in the research. Seven high-level health professionals participated in the study, two of whom were physicians, two nurses, one Odontologist, one Pharmacist and one Social Worker. The results indicate that adequate working conditions are lacking for the development of the tasks required in some units. The lack of professionals in the minimum team, such as a doctor, a nurse and a dentist, was detected. The reality of not having adequate working conditions related to equipment, instruments and even medicines causes in the professionals, a feeling of impotence before the sanitary framework and the great demand of users who seek for quality care and for the resolution of their health problems . With regard to the contribution of professionals to the organization of work, it was possible to verify the ingenious nature of the professionals who face the challenges, daily variabilities of users, equipment, working conditions, inputs, etc., engender forms of confrontation and activate Measures to ensure that the prescribed work takes place. Therefore, it shows the positivity of the work. The data show that the question of solvency seems to be a legal rule of this professional segment and that in order to reach it professionals are deployed to meet the demand that presents itself daily, even if it means subverting what was planned. On the other hand, work situations trigger feelings of guilt and / or impotence in health professionals in the face of service obstacles, which are not at the decision-making level of their daily work life. The research data show that the precariousness of the work is effective through the ways of hiring the professionals to work in the health units. Under the threat and fear of losing their jobs, of not receiving the salary, of not knowing if they will have vacations, of not being able to claim their rights, the temporary contracted professionals are impelled to accept passively the situation in which Lives in his work. Nevertheless, we can see that the work carried out by the multiprofessional teams also provokes positive situations both in relation to the recognition by the target public of the policy - the users, as well as the personal satisfaction of being working and developing their intellectual capacities for the improvement of the Conditions of the population.